Asset ownership along gender lines: evidence from Thailand - Rania Antonopoulos; Maria S. Floro (Levy Economics Institute of Bard College, 2005)
Gender differences have long been documented in earnings, employment opportunities, and time spent within the unpaid care economy. This paper joins the recent efforts in the economics literature on gender differences in asset ownership. Specifically, it investigates whether a gender-specific composition in asset ownership between heads of households and spouses can be detected among low-income, urban households in Bangkok, Thailand. The present case study explores this issue empirically, using a sample of 134 couples from a 2002 survey that collected data at the level of the individual respondent on accumulated physical and financial assets. Both husband and wife were interviewed separately and the data gathered from the interviews include pertinent household and individual information on employment, credit and household decisionmaking issues. The findings suggest that asset composition varies by gender, indicating that further investigation is warranted on this topic. Tobit and Probit tests are used to examine the factors that may affect this gendered pattern.
Keywords: D31; J16; O17; R29; 330; asset distribution; gender; Thailand